2022
DOI: 10.3389/fimmu.2022.939378
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Group 2 Innate Lymphoid Cells Defines Their Pleiotropic Roles in Cancer, Obesity, and Cardiovascular Diseases

Abstract: Group 2 innate lymphoid cells (ILC2s) are typically known for their ability to respond rapidly to parasitic infections and play a pivotal role in the development of certain allergic disorders. ILC2s produce cytokines such as Interleukin (IL)-5 and IL-13 similar to the type 2 T helper (Th2) cells. Recent findings have highlighted that ILC2s, together with IL-33 and eosinophils, participate in a considerably broad range of physiological roles such as anti-tumor immunity, metabolic regulation, and vascular disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 134 publications
(156 reference statements)
0
2
0
Order By: Relevance
“…S2J-L). Innate lymphoid cell (ILC)-2 are drivers of Th2 cytokine responses and are protective in obesity ( 31, 48, 49 ). ILC2 were present at small frequencies in the SVF in all groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S2J-L). Innate lymphoid cell (ILC)-2 are drivers of Th2 cytokine responses and are protective in obesity ( 31, 48, 49 ). ILC2 were present at small frequencies in the SVF in all groups (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In males, WT males SVF fibroblasts increased expression of prostaglandin transporter, Slco2a1 and stromal chemokine Cxcl12 , while KO males upregulated pathways involved in the inhibition of the antioxidative functions, resulting in the accumulation of reactive oxygen species and oxidative stress, such as Txnip . ILC2 are drivers of Th2 cytokine responses and are protective in obesity ( Brestoff et al, 2015 ; Ikutani and Nakae, 2022 ; Lee et al, 2015 ). ILC2 were present at small frequencies in the SVF in all groups ( Figure 5—figure supplement 2M–P ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, preclinical studies have reported protective effects of the expansion of ILC1s in the liver against NAFLD development and its consequences [23]. However, the role of ILC2s still remains imprecise and appears to affect, by either worsening or improving, NAFLD/obesity [24]. Many environmental factors have been studied and most of them appear to be related to ILC2s activation and the production of the profibrotic cytokine IL-13 affecting macrophage selective polarization.…”
Section: Discussionmentioning
confidence: 99%